Radial Transport of Energetic Electrons as Determined From the “Zebra Stripes” Measured in the Earth’s Inner Belt and Slot Region - Lejosne, Solène; Fejer, Bela G.; Maruyama, Naomi; Scherliess, Ludger (Frontiers in Astronomy and Space Sciences, 2022)
The “zebra stripes” are drift-periodic structures present in the form of peaks and valleys in energetic (tens to hundreds of keV) electron spectrograms in the Earth’s inner belt and slot region. Their characteristics inform of preceding electric field disturbances. Specifically, their amplitude contains information on the radial transport of trapped particles generated by azimuthal electric field disturbances. We introduce a method to quantify radial transport from the measured amplitude of the zebra stripes, and we apply it to the zebra stripes observed on 16 February 2014. The findings are compared with results from a particle tracing code that leverages an empirical analytical model for the electric field disturbances. The measured amplitude of the zebra stripes indicates that the electric field disturbances transported the trapped population coherently, over radial distances spanning several hundreds to thousands of kilometers. The magnitude of radial transport is shown to depend on angular drift frequency and initial location (equatorial radial distance and magnetic local time) in the disturbance. The model-observation comparison suggests that the timing for electric field variations provided by the model is valid for studying radial transport in the inner belt and slot region. On the other hand, we found discrepancies when comparing radial transport magnitudes. When assuming that radial transport varies as L^3, as weakly suggested by the data for set angular drift frequencies, and extrapolating observations to L=1, the amount of experimental transport obtained is two to three times greater than numerical estimates. Outputs from the standalone version of the Rice Convection Model (RCM) suggests that the electric field disturbances are likely greater than the estimates provided by the empirical model. RCM also supports the idea that radial transport driven by the prompt penetration of magnetospheric convection varies as L^3 in the inner belt and slot region.